2019
DOI: 10.2486/indhealth.2018-0065
|View full text |Cite
|
Sign up to set email alerts
|

How do we assess musicians’ musculoskeletal symptoms?: a review of outcomes and tools used

Abstract: Recent reviews of musicians’ musculoskeletal symptoms (MSS) have reported heterogeneity in the outcomes reported and data collection tools used, making it difficult to compare and synthesise findings. The purpose of this present review was to improve the consistency of future research, by documenting the outcomes reported in recent studies of musicians’ MSS and the data collection tools used. All English language, peer-reviewed studies, published 2007–2016 that reported musicians’ self-reported MSS outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 219 publications
0
24
0
Order By: Relevance
“…There are limitations to be aware of when considering our ndings. Firstly, although the location of MSK pain was determined according to a well-known and validated questionnaire -NMQ by Kuorinka et al (23) -in order to obtain standardised results which could be compared to other groups (12), speci c localised areas of the body such as ngers, were not contemplated as de ned by other methods (e.g. anatomical regions according to the Margolis rating or according to pain drawings).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limitations to be aware of when considering our ndings. Firstly, although the location of MSK pain was determined according to a well-known and validated questionnaire -NMQ by Kuorinka et al (23) -in order to obtain standardised results which could be compared to other groups (12), speci c localised areas of the body such as ngers, were not contemplated as de ned by other methods (e.g. anatomical regions according to the Margolis rating or according to pain drawings).…”
Section: Limitationsmentioning
confidence: 99%
“…It is plausible that this heterogeneity in the reporting of musicians' disorders may be attributed to the use of different methods of assessment (10,11), even though the Nordic Musculoskeletal Questionnaire (NMQ) remains the most commonly used questionnaire the analysis of MSK symptoms in the literature (12). The extent of variability between the anatomical regions included within the literature, is illustrated by reports recording from four (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of musicians’ MSSs have been investigated, and include pain, soreness, discomfort, ache, tension, clicking, popping, crepitus, tightness, stiffness, reduced range of motion, loss of motor control, cramp, muscle fatigue, loss of speed, loss of endurance, swelling, redness, burning, numbness and tingling. 14 Our review focuses specifically on pain because pain is the most commonly reported 15,16 and investigated 14 type of MSS among musicians. Musicians with MSSs, including pain, have reported experiencing a range of consequences in both musical and non-musical aspects of their lives.…”
Section: Introductionmentioning
confidence: 99%
“…3) There is a high prevalence of MSSs in professional musicians 4) which is reportedly higher than that of the general workforce 5) . Furthermore, musculoskeletal disorders account for 70% of all workers' compensation claims made by employed musicians 6) . Musculoskeletal symptoms may have a range of consequences for musicians, including having to take time off from work [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, musculoskeletal disorders account for 70% of all workers' compensation claims made by employed musicians 6) . Musculoskeletal symptoms may have a range of consequences for musicians, including having to take time off from work [5][6][7][8] . Research into musicians'…”
Section: Introductionmentioning
confidence: 99%